Alter-globalisation Social Imaginaries: a theoretical review - Yepez Reyes, Veronica (Imagonautas, 2019)
Social imaginaries refer not to something unreal or fictitious existing only in the mind of an individual, but to the shared frameworks within which people organise their collective social world. In the ubiquitous presence of the internet and the extended use of information and communication technologies (ICTs), market-oriented globalisation imaginaries have emerged, but also alter-imaginaries of globalisation sustained by advocacy organisations interconnected and spreading their concerns in the global sphere. This paper develops an exegetical analysis to establish the meaning and scope of social imaginaries and address along time the different approaches to this notion. The results show that despite their intangibility, social imaginaries are very ’real’, thus feigning permanence, social imaginaries are dynamic and in constant change.